Pengembangan Multimedia Pembelajaran Matematika dengan Model Blendd Learning - Nike Astiswijaya; Rahma Siska Utari (Jurnal Pendidikan Matematika : Judika Education, 2023)
This study aims to produce learning multimedia with the Blended Learning model on Opportunity material for Grade VIII students of SMP/MTs. The product to be made is learning multimedia using Microsoft Power Point which is then processed into videos, Google Classroom and Google Forms. This research was developed using the steps of the Tessmer model (1993). The stages carried out are the preliminary stage and the prototyping stage which consists of self evaluation, expert review, one to one, small group and field tests. The posttest results of students after carrying out mathematics learning with the Blended Learning model using learning multimedia in the form of learning videos, google classroom, google form show that 74% of students use multimedia learning mathematics that integrates learning videos, google classroom and google form and applies Blended Learning in one learning unit has been successful. In conclusion, learning multimedia developed using the Blended Learning model on opportunity material for Grade VIII junior high school students can be said to be valid, practical and successful in increasing students' posttest scores. Keywords: Learning Media, Multimedia, Opportunity, Development